Cleft Palate and Vascular Malformation in a Pediatric Patient With PIK3CA-related Overgrowth Spectrum. Issue 1 (15th December 2021) - Das, Rishub K.; Borst, Alexandra J.; Phillips, James D.
Abstract : Phosphoinositide-3-kinase, catalytic, alpha polypeptide-related overgrowth spectrum (PROS) encompasses a heterogenous group of disorders involving somatic mutations in the phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin pathway. The categories of PROS diseases continue to change as unique presentations and phenotype-genotype correlations are reported. These mutations result in progressive, segmental overgrowth of the affected tissue. Vascular malformations are common in PROS and represent a significant social and medical burden to patients, and in some cases, an increased risk for malignancy. Cleft palate, however, has not been reported. Herein, we describe a case of a 13-year-old girl with a variant of unknown significance in the PIK3CA gene who presents with a large capillary malformation, cleft palate, and right-sided hemihypertrophy.